Exploring Traditional Ecological Knowledge (TEK) as an Urgent Action to Combat Climate Change in Turkey - Seyfullah Gül (Coğrafya Dergisi)
The aim of this paper is to determine the role of traditional ecological knowledge (TEK) in coping with climate change and adapting to projected climate changes in the case of Turkey. In order to accomplish this research objective, we have set out to present TEK examples on themes such as (1) local climate information, (2) understanding climate change, (3) coping with climate change and developing adaptation strategies, and (4) correct management and protection of natural resources. This paper uses the qualitative research design of ethnographic research. The data were collected using qualitative data collection methods such as observations and interviews between 2018-2021, with the data analysis using the descriptive analysis technique. The purposeful sampling method of convenience sampling was used to select the places to be observed and the study group. This paper reveals the local communities to have developed TEK practices and strategies against climate change and the problems that arise as a result in Turkey. Integrating these TEK examples with scientific knowledge in Turkey is believed to be able to play an important role in climate change adaptation and mitigation.